Birdsong - Faulks, Sebastian (London : Vintage Books, 1994)
Rootless and heartbroken Stephen Wraysford joins the army at the outbreak of World War I and he and his men are given the assignment to tunnel under the German lines and set off bombs, where the camaraderie, love, and loyalty of the soldiers contrasts with the horrors of the underground, air, and trench warfare.
Adult.
Adult
Keywords: Soldiers -- Fiction; World War, 1914-1918 -- Fiction; Historical fiction; Love stories; Soldiers -- Fiction; War stories; World War, 1914-1918 -- Fiction; Historical fiction; Love stories; War stories